Synovial Metaplasia of the Endometrium. (28th October 2020) - Yurtsever, N; Truskinovsky, A
Abstract: Introduction/Objective: Synovial-like metaplasia is well known to accompany breast implants, but it can also rarely be found in the endometrium, associated with intrauterine devices. We present two cases of endometrial synovial-like metaplasia. Methods: The hysterectomy specimens were diagnosed at Northwell Health and reviewed at the departmental Consensus Conference. Immunostains for cytokeratin AE1/AE3 were performed on the endometrium. The histopathologic findings were correlated with the clinical information. Results: Both patients had had intrauterine devices placed for birth control. One, a 47-year-old female with a family history of Lynch syndrome and newly diagnosed with a corresponding mutation, underwent prophylactic hysterectomy. The second patient, a 50-year-old female with a history of uterine prolapse, was experiencing stress urinary incontinence, for which she underwent supracervical hysterectomy. Both patients had intrauterine devices in place at the time of hysterectomy. Both uteri showed endometrial synovial-like metaplasia. It was associated with a complete absence of the endometrial surface epithelium. The synovial-like cells were eosinophilic, plump and elongated, were palisaded perpendicular to the endometrial surface and were negative for cytokeratin AE1/AE3, which immunostain also confirmed the absence of the endometrial surface epithelium and the presence of some residual deeper endometrial glands. Conclusion: Endometrial synovial-like metaplasia is a rare entity described in patients with intrauterine devices. The mesodermal-derived endometrium is apparently able, when exposed to a semi-mobile foreign body, to develop a way to minimize friction by mimicking synovium, similar to the connective tissue facing breast implants. Such surface must be better at withstanding chronic friction than the regular endometrial epithelial surface, leading to this unusual and fascinating change. Since the resulting surface mimics synovium perfectly, both morphologically and immunohistochemically, and serves a very similar mechanical purpose, we propose to call this phenomenon, wherever it is found, "synovial metaplasia" instead of the current term "synovial-like metaplasia."